Effects of recreational soccer on physical fitness and health indices in sedentary healthy and unhealthy subjects - Hammami, A; Chamari, K; Slimani, M; Shephard, RJ; Yousfi, N; Tabka, Z; Bouhlel, E (Biology of Sport, 2016)
Recreational soccer (RS) is becoming a popular alternative to the classical continuous exercise mode used for the improvement of cardiovascular and metabolic fitness in untrained people. The objective of this paper was to conduct a detailed systematic review of the literature, identifying the physiological responses to RS and the training effects of RS on aerobic fitness and health in untrained healthy individuals and clinical patients. PubMed, Google Scholar and ScienceDirect databases were searched using terms related to recreational soccer. Inclusion criteria were randomized controlled trials (RCT) that assessed acute physiological responses to RS or the training effects of RS on physical fitness and health in sedentary, untrained subjects of any age or health status. All studies were assessed for methodological quality using the PEDro scale. Thirty-five articles met the inclusion criteria; seven examined the acute response to RS, and 28 assessed training effects. Clear evidence was found that RS had positive effects on many health-related indices and variables, including VO2max (gains of 7-16%), blood pressure (reductions of 6-13 mmHg), body composition (decreased fat mass and improved indices of bone health), and metabolic and cardiac function. These positive effects were observed in both healthy individuals and clinical patients, irrespective of age or sex. Although this review provides clear evidence of the positive effects of RS on health, most studies had limitations of methodology (an average PEDro score < 6). Furthermore, many of the training studies were from a small number of research groups. Future studies should be extended to other countries and institutions to ensure generality of the results. Regular RS training leads to significant cardiovascular and muscular adaptations and gains of health both in sedentary individuals and clinical patients at all ages, suggesting that RS is a potentially highly motivational method to enhance population health.